IMPROVING THE EFFICIENCY OF ASSET MANAGEMENT OF SPHERE OF SERVICES THROUGH HIGH-QUALITY AND SUBSTANTIATED INFORMATION - V. Mironenko; Y. Slinyakov (Вестник университета)
The main approaches to asset management of sphere of services through high-quality and substantiated information are has been considered. The current practice use fixed assets has been analysed. It is observed that the share of basic production assets varies across industries and depends on the specifics of each individual industry. In the total volume of property in such areas as transport, construction, the share of fixed assets is respectively 97 % and 90 %, which causes the need to clarify information about them. That is why the formation of a system of accounting and analytical support for the management of the process of operation of fixed assets has an important role in the management information.